Causal Association Between Tea Consumption and Kidney Function: A Mendelian Randomization Study - Zhang, Yangchang; Xiong, Yang; Shen, Shisi; Yang, Jialu; Wang, Wei; Wu, Tingting; Chen, Li; Yu, Qiuhua; Zuo, Hangjia; Wang, Xu; Lei, Xun (Frontiers in Nutrition, 2022)
Background: The causal association between tea consumption and the risk of chronic kidney disease (CKD) is few. This study was conducted to identify the potential causal effects of tea consumption on CKD, glomerular filtration rate (eGFR), and albuminuria Methods: The Genome-wide association studies (GWAS) from UK Biobank were available to identify single nucleotide polymorphisms (SNPs) associated with an extra daily cup of tea intake. The summary statistics for CKD, eGFR, and albuminuria from the CKDGen consortium with 133,814 participants (12,385 cases of CKD) of mostly European ancestry. Two-sample Mendelian randomization (MR) analyses were performed to test the effects of the selected SNPs and the CKD risk. Results: 2,672 SNPs associated with tea consumption (P <5×10-8) were found, and 45 of which were independent and available SNPs in CKDGen. Drinking higher cups of tea per day referred to a protective effect against CKD G3-G5 (OR, 0.80; 95% CI, 0.67-0.95) and eGFR (β= 0.019 log mL/min/1.73 m2 per cup per day; P < 0.001). High tea consumption was also slightly associated with a higher risk of albuminuria (OR, 0.75; 95% CI,0.57-0.99) after excluding 2 SNPs responsible for directional heterogeneity (Cochran Q P= 0.02). Conclusion: There were causal associations of genetically predicted an extra daily cup of tea intake with a reduced risk of CKD and albuminuria, and an increased level of eGFR.